PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MASA PANDEMI COVID 19 DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN - Fuadi, Ahmad Sahal; Muchson, M. (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The purpose of this study was to see the increase in learning activeness and learning outcomes of class XII students in Creative Products and Entrepreneurship subjects at SMK Hidayatus Sholihin using the Problem Based Learning (PBL) learning implementation model. This research is a classroom action research (classroom action research) to solve problems in the classroom. The research was conducted in three cycles and each cycle was carried out a reflection on the action given. The data technique used observation sheets, learning outcomes tests, and documentation. The data analysis technique is using quantitative quantitative analysis techniques. The results showed that the implementation of learning using the Problem Based Learning learning model can improve learning activeness and learning outcomes of class XII students on PKK subjects at SMK Hidayatus Sholihin. This can be seen from the activeness of students from the first cycle of 62.01%, an increase to 76.30% in the second cycle and an increase in the third cycle of 80.19%. The learning outcomes of students' knowledge can be seen from the class average score in cycle I of 76 with a 50% proportion of completeness and an increase in the second cycle of the class average to 80 with the proportion of completeness of 64% and an increase in cycle III the class average to 84 with the proportion of completeness 86%.